Intervention curatoriale et écologie symbolique : « A Few Degrees More Will Turn the World into an Uncomfortable Place » dans la collection du Musée Léopold - Béraud, Indira (Muséologies)

(untitled) (Association Québécoise de Promotion des Recherches Étudiantes en Muséologie (AQPREM), 2026)
This article examines the instrumentalization of works of art in certain contemporary museum settings for communication purposes, particularly as related to ecological issues. It is based on a critical analysis of the museum intervention «A Few Degrees More Will Turn the World into an Uncomfortable Place,» produced in partnership with the Climate Change Centre Austria and the Wien Nord Serviceplan communications agency, and involving the permanent collection of the “Vienna 1900. Birth of Modernism” exhibition at the Leopold Museum (Vienna). Enacted in response to the actions of environmental activists targeting the museum, the curatorial gesture involved altering the manner of hanging of some fifteen works from the collection that represent landscapes destined to disappear. The works, dispersed throughout the exhibition, were hung at an angle, prompting visitors to tilt their heads to contemplate them. Varying from 1.5° to 7°, the inclination represents concretely the predicted rise in temperatures relative to pre-industrial levels. The methodology adopted is based on a critical reading of the display and its effects on reception, a study of the labels and signage, and an analysis of the narrative conveyed by the exhibition and its impact on institutional positioning. In particular, the article highlights the divergence between the ecological mediation proposed by the institution and the depoliticization of the complex issues linked to the climate crisis.